PENGARUH KUALITAS PRODUK, HARGA DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN JANJI JIWA COFFEE CITRA RAYA - Amo Sugiharto; Mohamad Fajar Darmawan (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2021)
The purpose of this study was to determine the effect of product quality, price and service quality on the purchasing decision of Jiwa Coffee Citra Raya. This study uses quantitative methods. This research uses causal associative research. Respondents in this study amounted to 120 people. Sampling in this study used a non-probability sampling method. The method of data analysis in this study is to use the validity test, reliability test, and t test. Based on the results of the analysis and discussion that have been described previously, several conclusions can be drawn from the overall research results, namely: 1) Product quality has a significant influence on purchasing decisions. This means more product innovations that give the product superiority; 2) Price has a significant influence on the purchasing decision of Promise Jiwa Coffee in Citra Raya; and 3) Service quality has a significant influence on the purchasing decision of the Promise Jiwa Coffee in Citra Raya.